Analyzing the Macro-Economic and Employment Implications of Ambitious Mitigation Pathways and Carbon Pricing - Fragkos, Panagiotis; Fragkiadakis, Kostas (Frontiers in Climate, 2022)
The recent EU Green Deal puts forward ambition climate targets aiming to make the EU the first climate neutral continent by mid-century while ensuring a just transition. This requires a large-scale transformation of the EU and global energy and economic systems induced by both regulatory and market-based policies, in particular carbon pricing. Macro-economic models currently used for the analysis of climate policy impacts need improvements to consistently capture the transition dynamics and challenges. The study presents the methodological enhancements realized in general equilibrium model GEM-E3-FIT (including enhanced energy system representation, low-carbon innovation, clean energy markets, technology progress, policy instruments) to improve the simulation of the impacts of ambitious climate policies. The model-based analysis shows that high carbon pricing has limited negative impacts on the EU GDP and consumption, while leading to an economy transformation towards a capital-intensive structure triggered by increased investment in low-carbon technologies and energy efficient equipment. Global decarbonization to achieve the well-below 2oC goal of the Paris Agreement will modestly impact total employment, but its effects are pronounced on specific sectors which are impacted either negatively (e.g. supply of fossil fuels, energy intensive industries) or positively by creating additional jobs (e.g. low-carbon manufacturing, electricity sector).